A apresentação de “Maria” (A Tupansy) aos índios do Brasil: o Auto da Assunção como instrumento catequético em José de Anchieta no final do Séc. XVI. - Soriano, Felipe de Assunção (2020)
The mission of Our Lady of the Assumption in Rerigtibá, founded by Joseph de Anchieta on August 15, 1579, has got a strong influence of his personality, as an adept of having several theatrical experiences. For the inauguration of this church mission and the enthronement of his patron saint, Joseph de Anchieta prepared a self-Catechetical illustration that was staged on August 15, 1590. Owing to its historical, cultural and theological elements, we can perceive that his self-made work revel the best results from the indigenous ministry of the Society of Jesus in the 16th century. The hybridism of his popular Mariology, the allegorical and theatrical elements that he has employed do confess his transcultural method of catechism. Such creativity offers us an image of Mary established in the Patristic Traditions accommodated by the indigenous cultures and in the remote political elaborations of the colonial period. In accordance with his schema, the Mary of Anchieta will exercise the crucial role in the distant interior places directly collaborating in the conversion of the native people from the various nations gathered in this mission. And thus, from the hybrid and indigenous elements, our interest is to demonstrate how Joseph de Anchieta presents Mary (the Tupansy) to the natives of Brazil.